Association of the serum myeloperoxidase/high-density lipoprotein particle ratio and incident cardiovascular events in a multi-ethnic population: Observations from the Dallas Heart Study. (August 2017) - Khine, Htet W.; Teiber, John F.; Haley, Robert W.; Khera, Amit; Ayers, Colby R.; Rohatgi, Anand
Abstract: Background and aims: Myeloperoxidase (MPO), a product of systemic inflammation, promotes oxidation of lipoproteins; whereas, high-density lipoprotein (HDL) exerts anti-oxidative effects in part via paraoxonase-1 (PON1). MPO induces dysfunctional HDL particles; however, the interaction of circulating levels of these measures in cardiovascular disease (CVD) has not been studied in humans. We tested whether serum levels of MPO indexed to HDL particle concentration (MPO/HDLp) are associated with increased CVD risk in a large multiethnic population sample, free of CVD at baseline. Methods: Levels of MPO, HDL-C, and HDL particle concentration (HDLp) by NMR were measured at baseline in 2924 adults free of CVD. The associations of MPO/HDLp with incident ASCVD (first non-fatal myocardial infarction, non-fatal stroke, coronary revascularization, or CVD death) and total CVD were assessed in Cox proportional-hazards models adjusted for traditional risk factors. The median follow-up period was 9.4 years. Results: Adjusted for sex and race/ethnicity, MPO/HDLp was associated directly with body mass index, smoking status, high-sensitivity C-reactive protein, and interleukin 18, and inversely with age, HDL-C levels, HDL size, and PON1 arylesterase activity, but not with cholesterol efflux. In fully adjusted models, the highest versus lowest quartile of MPO/HDLp was associated with a 74% increase in incident ASCVD (aHR, 1.74, 95% CI 1.12–2.70) and a 91% increase in total incident CVD (aHR, 1.91, 95% CI 1.27–2.85). Conclusions: Increased MPO indexed to HDL particle concentration (MPO/HDLp) at baseline is associated with increased risk of incident CVD events in a population initially free of CVD over the 9.4 year period. Highlights: Increased serum levels of MPO indexed to HDL particle concentration (MPO/HDLp ratio) reflect increased state of inflammation. The MPO/HDLp ratio is directly associated with CVD risk in people who are free of CVD at baseline. Compositional assessment of dysfunctional HDL may be necessary to understand the role of HDL in atheroprotection.